Exposição ocupacional a patógenos sanguíneos entre profissionais de saúde: estudo transversal em centros cirúrgicos de uma capital brasileira - Leila de Fátima Santos (2021)
Health professionals are regularly exposed to potentially contaminated organic samples. This study aims to identify the occurrence of accidents and the odds ratio of accidents among health professionals, divided into two groups, physicians and non-physicians, who work in the general and obstetric surgical centers of three general teaching and reseach hospitals, located in Belo Horizonte, State of Minas Gerais. A cross-sectional survey was carried out with 640 health professionals who accepted the invitation to participate in the study, by signing an informed consent form. Data collection was carried out in the work environment through a structured questionnaire, consisting of 47 questions, referring to the characterization of the sample through socio-demographic and occupational data, prevention habits, the exposure itself and monitoring and post-exposure prophylaxis. For statistical analysis were used Chi-Square, Fisher's Exact and Binary Logistic Model. Comparison of quantitative variables between two groups (professional categories) was assessed using the Wilcoxon Mann-Whitney test. Among 640 professionals, 58.6% physicians and 41.1% non-physicians, 32% reported having suffered accidents, being the medical professional group (40.1%) the most affected. As the professional increases in age, the chance of having an accident with biological material decreases (p = 0.001; OR 0.55; 95% CI; 0.39-0.79). Regarding working time, it was observed that as the professional increased the time working in the institution, the chance of an accident with biological material increased (p < 0.001; OR 2.05; 95% CI; 1.49 -2.81). Professionals who consider it adequate showed a lower chance of having an accident with biological material (p < 0.001; OR 0.27; 95% CI; 0.14-0.49), thus, considering the appropriate protocol was considered a protection factor. In addition, health professionals who did not know how to give their opinion regarding the protocol showed lower chance of having an accident when compared to professionals who considered it inadequate (p < 0.001; OR 0.30; 95% CI; 0.16-0.56). It was also observed that the level of study and length of service were not able to guarantee the prevention of accidents with biological material, in addition to little knowledge regarding the notification rules and the care flow. Physicians and non-physicians professionals showed not only a significant incidence of accidents, but also a similar behavior profile in face of the event, with low notification and underestimated risk of the accident. It can be concluded that there is a latent need for more effective preventive measures, in addition to intrinsic motivations for work, greater encouragement to the work of workers' health care services, endorsing the relevance of occupational examinations.